Collaborative entrepreneurship, diversity management, and entrepreneurial performance of small and medium scale firms in Nigeria - Obinna Christian Ojiaku; Nkechi C. Ojiagu; Obianuju E. Agbasi (International Journal of Financial, Accounting, and Management, 2020)
Purpose: This paper investigates the effects of collaborative entrepreneurship and diversity management on entrepreneurial performance. Research methodology: A cross-section survey of 110 employees from the construction and auto-service SME in Nigeria was adopted, and multiple regression analysis via SPSS version 15 was used to analyze the hypothesized relationships. Results: The result shows a statistically significant relationship for external collaborative entrepreneurship and diversity management on firm performance. Limitations: The inability to collect data from all the major cosmopolitan cities in Nigeria where a larger pool of ethnically- diverse workforce resides limits the generalizability of the finding. Contribution: Entrepreneurs and small and medium scale enterprises in construction and auto works will find this work useful for effective collaboration. Keywords: Entrepreneurship, Collaboration, Diversity management, Ethnicity, Performance, Nigeria